Revision of the Australian species of Figulus MacLeay, 1819 (Coleoptera: Lucanidae) - Monte, Cinzia; Zilioli, Michele; Bartolozzi, Luca (Zootaxa, 2016)
The Australian species of the genus Figulus MacLeay, 1819 (Coleoptera: Lucanidae: Lucaninae: Figulini) are reviewed. Four new synonymies are established: F. howei De Lisle, 1967 and F. tambourinensis Mjöberg, 1916 are junior synonyms of F. nitens Waterhouse, 1874 (new synonymy); F. laevithorax Bomans is a junior synonym of F. regularis Westwood, 1834 (new synonymy); F. mento Albers, 1883 and F. mento foveatus Kriesche, 1922 are junior synonyms of F. sulcicollis Hope in Westwood, 1845 (new synonymy). The number of Figulus species known from Australia thus decreases to seven, four of which are endemic to Australia and one to Christmas Island. Lectotypes are designated for F. australicus Thomson, 1862, F. clivinoides Thomson, 1862, F. nitens Waterhouse, 1874, F. rossi Gahan, 1900, and F. tambourinensis Mjöberg, 1916. All the seven valid species are redescribed and a key is given for their identification. Photographs of the habitus, the mentum and illustrations of the aedeagus for all the taxa are also included. New unpublished data on the host plants and habitats for some of the Australian species are included.